Evaluation of Essential Oils and Phenolic Compounds of Some Origanum (Labiatae/Lamiaceae) Taxonomy - Gulsoy, Serkan (Asian Journal of Chemistry, 2012)
In present study, essential oils and phenolic compounds of five Origanum species, namely, Origanum onites, Origanum vulgare subsp. hirtum, Origanum minutiflorum, Origanum majorana and Origanum syriacum var. bevanii were analyzed and compared for their taxonomical importance. The data obtained from essential oil and phenolic compounds analyses were also addressed to find any correspondence with the taxonomic order of the five species based on morphological data. The relationships between Origanum taxa were analyzed by using T-rex programme. Reticulograms produced from both phenolics and essential oil data indicated that chemotaxonomic order of Origanum taxa based on essential oils data is more congruent with the taxonomic order of the same taxa based on Iestwaart's classification. In both reticulogram, Origanum vulgare subsp. hirtum was placed distantly from other Origanum species, this may be because this species is herbaceous while others are semi-shrubs.